Inteligentna linia analityczna jako platforma budowy systemów wczesnego ostrzegania w strategicznym zarządzaniu organizacją gospodarczą - Kostrubała, Sebastian; Stolecki, Grzegorz; Twardowski, Zbigniew (The Intelligent Analytical Line as a Platform for Developing of Business Early Warning Systems, 2005)
In this paper authors propose a new architecture for supporting strategic decision processes. Proposed platform contains analytical solutions and software toolkit which could be used for developing of early warning systems. The most challenging issue is to integrate set of technologies, tools and applications into one functional, easy operated decision support environment. In the presented version of intelligent analytical line we have included a new component: hybrid expert system with agents solving parts of the main decision problem. Our current researches prove that supporting of decision processes by combination of artificial intelligence and OLAP technologies is very well promising development.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 212-225